Characterising a potential nearshore nursery ground for the blackchin guitarfish (Glaucostegus cemiculus) in Ma’agan Michael, Israel - Barak Azrieli; Eynav Cohen; Leigh Livne; Debra Ramon; Anat Tsemel; Eyal Bigal; Eli Shemesh; Ziv Zemah-Shamir; Adi Barash; Dan Tchernov; Aviad Scheinin (Frontiers in Marine Science, 2024)
The blackchin guitarfish Glaucostegus cemiculus has suffered severe declines and regional extirpation throughout its known distributions. While this species and its relative, the common guitarfish Rhinobatos rhinobatos , have been described in the Mediterranean Sea with co-occurring habitat ranges, no research has recorded the existence or extent of these two separate populations along the Israeli coastal waters. Along a particular coast in Israel, Ma’agan Michael, fishermen have reported annual observations of juvenile guitarfish between June to November for the last forty years. Based on these citizen-based observations the main research objective is to establish whether Ma’agan Michael fulfils all three criteria from the literature by Dr Michelle Heupel, allowing it to be acknowledged as a nursery ground for G. cemiculus . The methodology built for this objective integrates biological characteristics data with the identification of a recurrent seasonal distribution. Visual surveys exhibited a significantly higher abundance in Ma’agan Michael when compared to an adjacent area (Caesarea), with 2,096 recorded observations overall. Additionally, using a species-specific modified Catch and Release protocol, a total of 492 juveniles were captured with a beach seine net. During these capturing events, individuals were morphometrically measured and sampled for future genetic analyses. Out of these, 327 specimens were also fitted for PIT tags to track recaptures in subsequent captures. The highest abundance of neonates was caught from August to September each year (2017–2019), and all individuals captured during this study were identified in the field as G. cemiculus , ranging from 20–35 cm in length (85% of captures). Many specimens had an umbilical cord scar (n = 88), with a large percentage possessing visual remains of the yolk sac. For the first time, this study provides an inter-year description of the species Glaucostegus cemiculus present along the Israeli shoreline.

Abstracts of Presentations at the 18th Conference of the Entomological Society of Israel - M. P. Pener; L. Anshelevich; E. Dunkelblum; M. Hard; A. Harari; D. Gordon; M. Kehat; H. Reuveny; O. Akunis; D. Oppenheim; E. Dunkelblum; Acta Rafaeli; et al. (Phytoparasitica, 2001)